Experimental optimisation of power for large arrays of cross-flow tidal turbines. (February 2018) - Sutherland, Duncan; Ordonez-Sanchez, Stephanie; Belmont, Michael R.; Moon, Ian; Steynor, Jeffrey; Davey, Thomas; Bruce, Tom
Abstract: As commercial scale tidal energy devices are shortly to be deployed in the first arrays, the knowledge of how different array layouts perform is a key and under-examined field. Here, the Momentum Reversal Lift (MRL) turbine, developed by the University of Exeter, is deployed in five different array layouts utilising up to 15 devices. The use of dynamic turbines allows the inclusion of analysis of the effects of flow direction in the wake. The layouts investigated explore the effect of lateral and stream-wise turbine spacings as well as differences between staggered and in-line layouts on power. The staggered array with decreased streamwise spacing is shown to have the highest total power per 'footprint' area among the layouts tested. For the staggered arrays, increased downstream separation had little effect on total power generated, while decreasing the lateral spacing below 2 rotor diameters decreased the power. The in-line arrays showed a lower power per device but similar total power. It was also shown that increased in-flow into a turbine didn't necessarily lead to an increased power extraction. The decrease in power with a decrease in streamwise spacing is in-line with theoretical and CFD predictions. Highlights: Largest physical testing of dynamic arrays of tidal turbines. Spacing between turbines affects power output by up to 19% per device in the tested configurations. Increasing streamwise spacing increases the total power captured. Staggering rows generally improves the power per device . A decrease in lateral spacing below two turbine diameters decreases in power .